Implementing Bakiak: A traditional game to improve the cooperative ability of children aged 5-6 years’ old - Ayu Susanti, Nur; Afiif, Ahmad; Damayanti, Eka (Journal of Early Childhood Care and Education, 2023)
Since the Covid-19 pandemic, children’s play activities have been limited so they have less interaction with their peers. This may give a negative impact because children will be individualists and the ability to cooperate is not formed. Therefore, we need a game that encourages children to cooperate with their friends. The purpose of this study was to improve the cooperative ability of children aged 5-6 years through traditional clog games in Paso’tane Hamlet, Belabori Village, Parangloe District, Gowa Regency. The research method used pre-experimental, with a one-group pretest post-test research design. The population of this study were all children aged 5-6 years in Paso’tanae Hamlet, consisting of 8 children. The number of samples used were 8 children. The sampling technique used was saturated sampling so that the entire population becomes the sample. The instrument used in this study is the observation sheet. Data analysis used non-parametric statistics using the Wilcoxon ranking test. The results showed a significant difference between the pretest and posttest with a p-value of 0.012 (≤ 0.05). The average pretest score was 26.62 and the post-test score increased to 42.5. This means that there was an increase in the average score between the pretest and posttest in the cooperative ability of children aged 5-6 years through the implementation of traditional bakiak games in Paso’tanae Hamlet, Belabori Village, Parangloe District, Gowa Regency. The results of the findings can be a recommendation to apply various traditional games as a medium for playing for children and preserving local culture.